2007
DOI: 10.1016/j.bmc.2007.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Novel, potent THC/anandamide (hybrid) analogs

Abstract: The structure activity relationship (SAR) of the end pentyl chain in anandamide (AEA) has been established to be very similar to that of Δ 9 -tetrahydrocannabinol Δ 9 -THC). In order to broaden our understanding of the structural similarities between AEA and THC, hybrid structures 1-3 were designed. In these hybrids the aromatic ring of THC-DMH was linked to the AEA moiety through an ether linkage with the oxygen of the phenol of THC. Hybrid 1 (O-220) was found to have very high binding affinity to CB1 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Furthermore, tetrad effects observed with the combination of NAM and 2-AG were significantly attenuated by the CB 1 -selective antagonist SR141716A, but unaffected by the CB 2 -selective antagonist SR144528. These results are consistent with a large body of research demonstrating that cannabinoids of various classes, including AEAs (when metabolism is inhibited), THC-like cannabinoids, bicyclic cannabinoids, and aminoalkylindoles, produce dose-dependent and CB 1 -mediated effects in these tests (Compton et al, 1992a,b; Compton and Martin, 1997; Bourne et al, 2007; Wise et al, 2007). …”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, tetrad effects observed with the combination of NAM and 2-AG were significantly attenuated by the CB 1 -selective antagonist SR141716A, but unaffected by the CB 2 -selective antagonist SR144528. These results are consistent with a large body of research demonstrating that cannabinoids of various classes, including AEAs (when metabolism is inhibited), THC-like cannabinoids, bicyclic cannabinoids, and aminoalkylindoles, produce dose-dependent and CB 1 -mediated effects in these tests (Compton et al, 1992a,b; Compton and Martin, 1997; Bourne et al, 2007; Wise et al, 2007). …”
Section: Discussionsupporting
confidence: 88%
“…Licensed drugs target cannabinoid receptors for treating chemotherapy-induced nausea and vomiting, relieving neuropathic pain, and as an appetite stimulant for AIDS patients [4]. Drugs targeting CB1 receptor are continually being developed [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Coupling constants are reported in Hertz [Hz]. 13 C NMR spectra were fully decoupled and are referenced to the middle peak of the solvent CDCl 3 at δ = 77.0 ppm. Splitting patterns are designated as: s, singlet; d, doublet; t, triplet; q, quadruplet; qn, quintet; dd, double doublet, etc.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] A recent report, based on molecular modelling studies, have shown that FAAH selectively accommodates anandamide into a multipocket binding site and confirmed that the rate of substrate hydrolysis increases with the number of double bonds within the substrate lipid chain. [16] Keeping in mind the above data, we focused on the use of linolenoyl and arachidonoyl derivatives as putative FAAH substrates.…”
Section: Introductionmentioning
confidence: 97%